Effect of Quenching Media on Distortion of C-Ring Specimen Made by 100Cr6 Steel - Simulation and Experiment - Tran, Thi Xuan; Nguyen, Van Tu; Le, Thi Chieu; Vu, Dinh Toai (Old Journal, 2017)
Polymer quenchants based on polyalkylene glycols (PAG) are currently the most widely used type of aqueous quenchants. In this paper, the numerical simulation method by Sysweld software was used to predict the distortions of C-ring model using 100Cr6 steel when quenched in the difference media. The simulation results are in good agreement with the experimental values, and they also showed that the top of C-ring was opened after deformation. The gap opening of C-ring specimens when quenched in PAG 20% solution is the smallest in comparison to the specimens quenched in water, oil and PAG 10% solutions. On the other hand, the research results also show that the distortion at the top of C-ring is the largest and they are decreased from the top downward the bottom of C-ring.